Analysis of Commisive Speech Act in Moanna The Movie - Wulandary, Hardyanti (Al'Adzkiya Journal, 2022)
This study aimed to describe the types and functions of commissive speech acts found in Moana the movie. Moana is an animated movie about the adventure that was released in 2016 and produced by Walt Disney Pictures. This movie tells about the adventures of the chief's daughter who will become the leader of the Motunui village. She wanted to prove to the villagers that she deserved to be a good leader for them. She must find Maui and work together to restore Te Fiti's heart. The things shown in the movie are about how Moana wants to prove herself to others about what she said. Therefore commissive speech acts are found in the movie. The research data was taken from the Moana movie. The researcher uses the observation method to determine the data to be analyzed. The purposive sampling method is used to take data samples. Data collection is done by watching the movie carefully, then make note-taking and grouping the data into commissive speech based on the theory of George Yule (1996). The researcher then analyzes the data based on its function. The results of this study are there are 18 data of commissive speech acts found in the Moana movie in the form of 5 data functioning to promise, 4 data functioning to threat, and 9 data functioning to refuse.